Peran BUMDesa Podo Makmur melalui Unit Peternakan untuk Meningkatkan Perekonomian Desa Kandangan Kecamatan Srengat Kabupaten Blitar - Abdul Aziz Al Kaharudin (Studi Administrasi Publik dan ilmu Komunikasi, 2025)
This research was inspired by Bumdesa Podo Makmur, which is an initiative of the village government to improve the community's economy, including educating the public about BUMDes, planting and raising various types of livestock, and running trade and other businesses. There are still individuals who have not joined and taken advantage of BUMDes institutions even though business units are available. The qualitative research methodology used. Data collection methods include documentation, interviews, and observations. Data analysis methods include data reduction, data visualization, data validation, and conclusion drawn. The results of the research are 1) The efforts of the Podo Makmur Kandangan bumdesa in the livestock unit in Kandangan Village, namely improving the quality in the management structure and management of bumdes so that the performance of bumdes managers is getting better. Increasing collaboration with farmer organizations and strengthening social capital capacity, especially in terms of trust and networks to develop livestock business units, is very important in addition to strengthening the management structure of BUMDes. The next step is to try to increase farmers' trust in Bumdes by making the company more open, honest, and honest. 2) The contribution of the Podo Makmur Kandangan bumdesa through the livestock unit to improve the economy in Kandangan Village by carrying out its programs to improve the business units run, especially the livestock unit; helping the community through education, guidance and business improvement training provided by Budes every two months to ensure the proper running of business programs; Assists in organizing, managing, repairing, and supervising the enclosure. This helps goat farms breed and produce livestock products that can be used by many people.